2020
DOI: 10.1111/eva.12943
|View full text |Cite
|
Sign up to set email alerts
|

Agent‐based modelling reveals strategies to reduce the fitness and metastatic potential of circulating tumour cell clusters

Abstract: Metastasis—the ability of cancer cells to disperse throughout the body and establish new tumours at distant locations—is responsible for most cancer‐related deaths. Although both single and clusters of circulating tumour cells (CTCs) have been isolated from cancer patients, CTC clusters are generally associated with higher metastatic potential and worse prognosis. From an evolutionary perspective, being part of a cluster can provide cells with several benefits both in terms of survival (e.g. protection) and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 69 publications
0
15
0
Order By: Relevance
“…Ongoing trials are seeking to reconcile and elucidate these findings by looking at correlations between chemotherapy treatment and disease subtype to better understand the effect on CTCs. However, in a model-based study of CTC clusters, clusters are more resistant to single-point attacks than single CTCs [ 87 ]. As such, CTC clusters are less likely to be impacted by chemotherapy treatment alone and instead will be more susceptible to combination attacks that reduce both their resources and increase their environmental threats.…”
Section: Ctcs Serve As a Novel Therapeutic Target For Many Different Cancersmentioning
confidence: 99%
See 1 more Smart Citation
“…Ongoing trials are seeking to reconcile and elucidate these findings by looking at correlations between chemotherapy treatment and disease subtype to better understand the effect on CTCs. However, in a model-based study of CTC clusters, clusters are more resistant to single-point attacks than single CTCs [ 87 ]. As such, CTC clusters are less likely to be impacted by chemotherapy treatment alone and instead will be more susceptible to combination attacks that reduce both their resources and increase their environmental threats.…”
Section: Ctcs Serve As a Novel Therapeutic Target For Many Different Cancersmentioning
confidence: 99%
“…As such, CTC clusters are less likely to be impacted by chemotherapy treatment alone and instead will be more susceptible to combination attacks that reduce both their resources and increase their environmental threats. The mentioned study also showed that high-density clusters are further protected from changes in resource availability or environmental threats, suggesting that, although these populations are rare, they are also extremely dangerous [ 87 ].…”
Section: Ctcs Serve As a Novel Therapeutic Target For Many Different Cancersmentioning
confidence: 99%
“…Such perturbations can lead to reduced tumour growths and disease burdens (Zhang et al, 2017; Dominiak et al, 2020; Brücher and Jamall, 2014; West and Newton, 2019). Cell-cell interactions, and the impact that they have on cancer system dynamics, have been mathematically studied by researchers using a variety of mathematical models including evolutionary game theory (EGT) models (Zhang et al, 2017; Kaznatcheev et al, 2019; Archetti et al, 2015), other ordinary differential equation (ODE) models (Hillen et al, 2013; Poleszczuk and Enderling, 2018; Jenner et al, 2018), partial differential equation (PDE) models (Haridas et al, 2017; Lorenzi et al, 2017; Hinow et al, 2009), and individual-based models (IMBs) (Stichel et al, 2017; Campenni et al, 2020; Hamis et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Cancer metastasis is a major cause of cancer-related mortality. Compared to single cancer cells, tumor cell clusters have shown higher metastasis initiation capability. , Accordingly, dynamic analysis of tumor cell clusters is important for understanding how the metastatic potential of cancer might be reduced. Within a cluster, cellular plasticity and strong cell–cell connections confer higher cellular survival rates, greater proliferation, and resistance. Tumor cell clusters of various sizes and densities respond differently to resources or environmental changes, and cell survival and cluster stability under different conditions vary dramatically .…”
Section: Introductionmentioning
confidence: 99%
“…Within a cluster, cellular plasticity and strong cell–cell connections confer higher cellular survival rates, greater proliferation, and resistance. Tumor cell clusters of various sizes and densities respond differently to resources or environmental changes, and cell survival and cluster stability under different conditions vary dramatically . Therefore, the controlled generation of cell clusters of varying sizes and densities would allow a better understanding of the differences in metastatic potential among clusters . Although considerable research has been focused on the cluster size, the responses of clusters of different densities to particular conditions are still unknown.…”
Section: Introductionmentioning
confidence: 99%